Konsentrasi Paraquat dalam Urin Pekerja Akibat Paparan Paraquat di Perkebunan Kelapa Sawit - Maksuk, Maksuk - (Media Kesehatan Masyarakat Indonesia, 2019)
Paraquat is an active ingredient of herbicide, it is very toxic mainly in humans and can enter the body through ingestion, inhalation and skin. This study aimed to analyze paraquat exposure to paraquat concentrations in the urine of workers on palm oil plantations. This study used a cross sectional design, with a sample of 60 workers and randomly selected, urine was collected on the last day of paraquat spraying. Paraquat in urine was tested in a laboratory using High Performance Liquid Chromatography (HPLC) using the EPA 549.2 methods. Data were analyzed by univariate and bivariate using Mann Whitney test.The average of paraquat concentration in urine of men workers was 6.35 mg / L and women 6.55 mg / L, with a range between <0.25 - 35.75 mg / L. The results of Mann Whitney test showed that the difference of paraquat concentration in urine of workers was influenced by several variables, namely length of work (p=0.026), spraying method (p=0.048), eating / drinking during application (p=0.040), completeness of using personal protection equipment (p=0.03) and decontamination after spraying (p=0.026).This study provided evidence of paraquat presence in urine workers’. Therefore it is necessary to urine examination periodically.